Family Leisure, Self-Management, and Satisfaction in Spanish Youth - Alonso Ruiz, Rosa Ana; Valdemoros San Emeterio, María Ángeles; Sáenz de Jubera Ocón, Magdalena; Sanz Arazuri, Eva (Frontiers in Psychology, 2019)
Youth values leisure as a right, a source of growth and integral development, as well as a context for experimentation. It has been shown that organized leisure leads to more benefits than unorganized leisure; when undertaken by the young people themselves, these benefits lead to the development of prosocial skills, self-efficacy, autonomy, as well as increased independence, personal motivation, and responsibility, as well as acting as a protective factor against risky behaviors. When organized leisure activities are also shared with the family, the benefits influence a positive family environment. This study focused on analyzing the relationship between family-shared leisure practices that are managed by Spanish youth in post-compulsory secondary education, and the importance and satisfaction granted to these experiences. The sample consisted of 1764 post-compulsory secondary education students from all over Spain. Youth's responsibility for the organization of their leisure activities, the perception of the relationship between enjoyment of the activity and involvement in its management, the organization of the spaces in which leisure activities are carried out, their satisfaction with them, and the importance attached to shared practice and family experiences were recorded. The results showed a shortage of self-managed youth leisure practices, but increased responsibility, spatial organization, and satisfaction were confirmed when leisure experiences are shared with the family. The need to encourage opportunities for children to self-organize their leisure practices from an early age is commented on.